2014
DOI: 10.2147/ijn.s63873
|View full text |Cite
|
Sign up to set email alerts
|

Biological impact of superparamagnetic iron oxide nanoparticles for magnetic particle imaging of head and neck cancer cells

Abstract: Background As a tomographic imaging technology, magnetic particle imaging (MPI) allows high spatial resolution and sensitivity, and the possibility to create real-time images by determining the spatial distribution of magnetic particles. To ensure a prospective biosafe application of UL-D (University of Luebeck-Dextran coated superparamagnetic nanoparticles), we evaluated the biocompatibility of superparamagnetic iron oxide nanoparticles (SPIONs), their impact on biological properties, and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 55 publications
3
27
1
Order By: Relevance
“…14 In order to examine if the cytokine response in our study was accompanied by ROS production, we measured intracellular ROS in the whole blood samples after 2 and 4 h. The IONPs did not significantly increase ROS compared with the control samples, which is in agreement with previous findings. 30,31 However, our results are in contrast to other studies that show IONP-induced ROS production. [32][33][34][35] Possible explanations for the discrepancies include one or more of the following factors: different types and sizes of IONPs used; different surface properties (eg, surface coatings) of the IONPs that affect the degradation potential and thus the exposure to the naked iron oxide core and the liberation of iron ions that might induce ROS; 32 different cell types used; higher IONP concentration; different (mostly longer) incubation times after which ROS production was measured and/or different methods for assessing intracellular ROS.…”
Section: Discussioncontrasting
confidence: 99%
“…14 In order to examine if the cytokine response in our study was accompanied by ROS production, we measured intracellular ROS in the whole blood samples after 2 and 4 h. The IONPs did not significantly increase ROS compared with the control samples, which is in agreement with previous findings. 30,31 However, our results are in contrast to other studies that show IONP-induced ROS production. [32][33][34][35] Possible explanations for the discrepancies include one or more of the following factors: different types and sizes of IONPs used; different surface properties (eg, surface coatings) of the IONPs that affect the degradation potential and thus the exposure to the naked iron oxide core and the liberation of iron ions that might induce ROS; 32 different cell types used; higher IONP concentration; different (mostly longer) incubation times after which ROS production was measured and/or different methods for assessing intracellular ROS.…”
Section: Discussioncontrasting
confidence: 99%
“…Cell labeling and cell tracking are further very important applications for MPI 13 that potentially allow for direct imaging of cell movements in vivo. It has been shown that MPI can track the long-term fate of in vivo neural cell implants with high image contrast 14 .…”
Section: Introductionmentioning
confidence: 99%
“…38 Both the chemical composition and the nanostructure of the material are responsible for the characteristics exploited for several applications in biological sciences, such as superparamagnetism. 39,40 Biocompatible SPIONs, such as magnetite, have been widely used for in vivo biomedical applications. Their slower renal clearance and higher relaxation values compared with the gadolinium-based contrast agents make them more attractive for imaging purposes.…”
mentioning
confidence: 99%